2019
DOI: 10.1002/bdr2.1552
|View full text |Cite
|
Sign up to set email alerts
|

Survival of infants with spina bifida and the role of maternal prepregnancy body mass index

Abstract: Objective: To investigate first-year survival of infants born with spina bifida, and examine the association of maternal prepregnancy body mass index (BMI) with infant mortality. Methods: This is a retrospective cohort study of 1,533 liveborn infants with nonsyndromic spina bifida with estimated dates of delivery from 1998 to 2011 whose mothers were eligible for the National Birth Defects Prevention Study (NBDPS). NBDPS data were linked to death records to conduct survival analyses. Kaplan-Meier survival funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…We were also not able to examine mortality by level of lesion, which is a known predictor with ascending lesions significantly associated with mortality among infants with spina bifida. 10,15,23 In conclusion, our study had the lowest rate of infant mortality compared with prior studies, which were conducted during the postfortification years in the United States. We also examined early neonatal mortality among infants with myelomeningocele and factors associated with this outcome for the first time.…”
Section: Discussionmentioning
confidence: 49%
See 2 more Smart Citations
“…We were also not able to examine mortality by level of lesion, which is a known predictor with ascending lesions significantly associated with mortality among infants with spina bifida. 10,15,23 In conclusion, our study had the lowest rate of infant mortality compared with prior studies, which were conducted during the postfortification years in the United States. We also examined early neonatal mortality among infants with myelomeningocele and factors associated with this outcome for the first time.…”
Section: Discussionmentioning
confidence: 49%
“…Another study examining postfortification period in the United States for mothers, who were eligible for the National Birth Defects Prevention Study and with estimated dates of delivery from 1998 to 2011, found a significantly increased risk of infant mortality among spina bifida cases with multiple co-occurring birth defects, very preterm gestation, multiple gestation, high-level spina bifida lesions, and non-Hispanic Black mothers. 15 We found a protective association for infant mortality if the infant also had a diagnosis of congenital hydrocephalus. This contradicted a previous study where congenital hydrocephalus increased the risk of death in infancy among those with spina bifida.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Meta-analyses showed a dose-response association between maternal Body Mass Index (BMI) and NTDs, and the risk rapidly increased in women with a BMI ≥ 30 kg/m 2 ( Table 1 ) [ 4 , 5 , 6 ]. In addition, a BMI ≥ 30 kg/m 2 , defined as maternal obesity, is also associated with the severity of the NTD in the offspring [ 7 , 8 ].…”
Section: Rationalementioning
confidence: 99%
“…National campaign to promote maternal and child health in 21st-century Japan (Healthy Parents and Children 21) [2] has raised concerns regarding the nutritional status of women of reproductive age in Japan because the proportion of underweight in both junior high and high school girls in Japan has increased to 20% [3]. Previous publications suggested that children born to such underweight women had an increased risk of infant mortality [4,5]. A recent database study [6] with more than 90,000 pregnant women compiled by the Japan Society of Obstetrics and Gynecology Successive Pregnancy Birth Registry System demonstrated that underweight women are more likely to bear small babies.…”
Section: Introductionmentioning
confidence: 99%